Chile : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report, 2021)
Strong fiscal institutions have contributed to Chile's macroeconomic stability, and recent reform initiatives have focused on enhancing these institutions and fiscal transparency. This report assesses fiscal transparency practices in Chile in relation to the requirements of the IMF's Fiscal Transparency Code and confirms that many elements of sound fiscal transparency practices are already in place. Chile's practices meet the principles of the code at a good or advanced level for 21 out of the 36 principles. This is a good score, compared to the average for Latin American Countries and Emerging Market Economies. On a further nine principles, Chile meets the basic standard of practice. Chile's fiscal transparency practices are very strong for fiscal forecasting and budgeting, followed by fiscal reporting, while fiscal risk analysis and management demonstrate more mixed results. Further improvements could be achieved relatively easily through the publication of some internal analyses or through a more timely or user-friendly publication of already available information.